Update on neurological symptoms in patients infected with severe acute respiratory syndrome coronavirus‐2. Issue 4 (20th December 2021) - Xiao, Mei‐Fang; You, Zhi‐Jian; Zeng, Chang; Huang, Ze‐Bing; Dong, Liang
Abstract: Novel coronavirus 19 (COVID‐19) is the latest and most intense epidemic, which is caused by the severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2). In addition to causing respiratory symptoms, SARS‐CoV‐2 can have severe effects on the nervous system. Clinically, COVID‐19 patients have been reported ranging from mild hypogeusia and hyposmia to severe neurological disorders, such as encephalopathy, encephalitis, strokes, and seizures syndrome. However, the pathological mechanisms of this SARS‐CoV‐2 neuro aggressiveness remain unclear, so it is of great significance to explore the neurological effects of SARS‐CoV‐2 infection. To facilitate clinicians to timely recognize the manifestations of COVID‐19 patients with neurological injury and timely treatment, the author hereby reviews the latest research progress in the possible pathways, clinical manifestations, and pathogenesis of COVID‐19 patients with nerve injury. Abstract : Severe acute respiratory syndrome coronavirus‐2 can cause nervous system injury in the human body by direct, hypoxia, and immune injury, which affects a part of novel coronavirus 19 patients with strokes, seizures, myelitis, as well as other neurological complications.